2012
DOI: 10.1055/s-0032-1327774
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Pediatric Balance Scales in Children with Spastic Cerebral Palsy

Abstract: This study was performed to examine the convergent and discriminant validity of the Pediatric Balance Scale (PBS), a modified version of the Berg Balance Scale (BBS), in children with spastic cerebral palsy (CP). A total of 38 children (age, 4 to 10 years) with spastic CP who could ambulate participated in this study. PBS, equilibrium scores of Sensory Organization Test derived from computerized dynamic posturography, Gross Motor Function Measure (GMFM), and Pediatric Evaluation of Disability Inventory (PEDI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 22 publications
2
58
0
1
Order By: Relevance
“…A total of 14 functional balance tests were identified that were investigated in children . These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 functional balance tests were identified that were investigated in children . These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified.…”
Section: Resultsmentioning
confidence: 99%
“…These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified. A detailed description of the test modalities for each test is available in Appendix S1 (supporting information published online).…”
Section: Resultsmentioning
confidence: 99%
“…The GMFM-66 has been used in many studies of children with CP whose functional CP severities were classifi ed as GMFCS Levels I to III (e.g., Yi, Hwang, Kim, & Kwon, 2012 ). In the study by Oeffi nger, et al .…”
Section: Discussionmentioning
confidence: 99%
“…The order in which the measurement tools were applied was decided randomly by drawing a note with the name of the tool from a box. The evaluation of the second measurement tool was made at an interval of 15 minutes to enable the subjects to recover from any fatigue caused by the first evaluation13 ) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, prior research reported a statistically significant correlation (r=0.7) between the Gross Motor Function Measure (GMFM)-88 and PBS in Down’s syndrome children12 ) ; a high correlation between the PBS and GMFM (domains D and E: overall score of GMFM-88 and GMFM-66) was also reported in children with spastic cerebral palsy who were capable of walking13 ) . Moreover, a high correlation was noted in the overall scores of PBS and GMFM for walking velocity and a 10-second standing up from seated posture test6 ) .…”
Section: Introductionmentioning
confidence: 94%